2018
DOI: 10.1002/adbi.201800055
|View full text |Cite
|
Sign up to set email alerts
|

Fish Skin: A Natural Inspiration for Innovation

Abstract: Natural materials and the structures they form, developed and perfected through millions of years of evolution, have long inspired researchers for innovations in science and engineering. One example, fish scales are notable for their strength, toughness, flexibility, and lightweight. These properties are the result of collagen fibrils and hydroxyapatite crystals that have been arranged into three‐layer structures through mechanical locking and chemical bonds, via a process that is still poorly understood. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Fish scales are widely known to have excellent toughness, and this mechanism is one of the focus areas of the current research. The mechanical properties of the material are known to change between the hydrated and dry states (Drelich, Monteior, Brookins, & Drelich, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish scales are widely known to have excellent toughness, and this mechanism is one of the focus areas of the current research. The mechanical properties of the material are known to change between the hydrated and dry states (Drelich, Monteior, Brookins, & Drelich, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of the fish scales are known to change between the hydrated and dry states (Drelich et al, 2018). Lin, Wei, Olevsky, and Meyers (2011)) investigated the Arapaima scale by conducting a tensile test and found that the values differed significantly between both the states.…”
Section: Resultsmentioning
confidence: 99%
“…"One of the critical ingredients of innovation is the source of the idea or inspiration for the innovation" (Bommer and Jalajas 2004, p. 13). Idea generation has been attributed to inspiration both in general (Drucker 1999) and in relation to specific research areas (e.g., Drelich et al 2018;Mead et al 2020). Inspiration exists in new product development and design (Halskov and Dalsgård 2006;Vasconcelos et al 2017;Brun et al 2018) as well as in earlier stages of the innovation process.…”
Section: Introductionmentioning
confidence: 99%
“…From a materials perspective, characterization studies of various scales have revealed highly intricate microstructures. Such scales can be hybrid 1012 , hierarchical 1315 , and composite in nature 1618 capable of engaging multiple length scales depending on the load 1921 . Scales are also naturally multifunctional 22–25 .…”
Section: Introductionmentioning
confidence: 99%